Competitive Advantage in Cost Leadership and Differentiation of SMEs “Bakoel Zee” Marketing Strategy in BSD - Marissa Grace Haque; Munawaroh Munawaroh; Denok Sunarsi; Aris Baharuddin (Universitas Negeri Makassar, 2021)
The purpose of this study was to measure the strategy implementation of cost leadership and differrentiation to its competitive advantage in the SMEs culinary business. The design or method which is used in this study is a multiple linear regression statistical analysis by the independent variable (X) products Nasi Bakoel as Cost leadership (X1) and product Dimsum as Differrentiation (X2). While the dependent variable (Y) Total Sales as its competitive advantage. The findings of this study is simultaneously cost leadership and differentiation positive and significant impact on the competitive advantage, while individually the effect is greater than the cost leadership differentiation to competitive advantage. This research is also expected to be a reference for further studies with similar problems in the future.